A novel interleukin-2-based fusion molecule, HCW9302, differentially promotes regulatory T cell expansion to treat atherosclerosis in mice - Zhu, Xiaoyun; Li, Qiongzhen; George, Varghese; Spanoudis, Catherine; Gilkes, Crystal; Shrestha, Niraj; Liu, Bai; Kong, Lin; You, Lijing; Echeverri, Christian; Li, Liying; Wang, Zheng; et al. (Frontiers in Immunology, 2023)
Atherosclerosis is a chronic inflammatory disease caused by deposition of oxidative low-density lipoprotein (LDL) in the arterial intima which triggers the innate immune response through myeloid cells such as macrophages. Regulatory T cells (Tregs) play an important role in controlling the progression or regression of atherosclerosis by resolving macrophage-mediated inflammatory functions. Interleukin-2 (IL-2) signaling is essential for homeostasis of Tregs. Since recombinant IL-2 has an unfavorable pharmacokinetic profile limiting its therapeutic use, we constructed a fusion protein, designated HCW9302, containing two IL-2 domains linked by an extracellular tissue factor domain. We found that HCW9302 exhibited a longer serum half-life with an approximately 1000-fold higher affinity for the IL-2Rα than IL-2. HCW9302 could be administered to mice at a dosing range that expanded and activated Tregs but not CD4+ effector T cells. In an ApoE-/- mouse model, HCW9302 treatment curtailed the progression of atherosclerosis through Treg activation and expansion, M2 macrophage polarization and myeloid-derived suppressor cell induction. HCW9302 treatment also lessened inflammatory responses in the aorta. Thus, HCW9302 is a potential therapeutic agent to expand and activate Tregs for treatment of inflammatory and autoimmune diseases.